One Dimension Spring Supported Ball on Top of a Sinusoidal Vibrating Plate: A Forced Oscillation Simulation using Molecular Dynamics Method - Sparisoma Viridi; Wahyu Srigutomo; Alamta Singarimbun; Wahyu Hidayat; Sitti Balkis (Indonesian Journal of Physics, 2011)
A ball supported by a spring is set on top of a plate which is sinusoidal vibrated. The motion is limited to one dimension motion. It is assumed that the spring is an ideal one with zero mass. The vibrating plate is considered much heavier than the ball, so that the ball motion has no influence on the plate motion. Plate vibration frequency is varied around the frequency of ball-spring system. Resonance phenomenon is reported, which needs a phase match condition to occur.